Durable strategies for perovskite photovoltaics - Chong Dong; Zhao-Kui Wang; Liang-Sheng Liao (APL Materials, 2020)
Perovskite solar cells have experienced a flying enhancement in their efficiency, which presents great potentiality in the photovoltaic industry. However, perovskite (PVSK) degradation is a serious problem for viable and sustainable commercialization. Apart from the intrinsic structural instability, PVSK materials are apt to be influenced by the environment including electrical and chemical situations, moisture and oxygen, and light and heat. Here, we discuss the corrosion mechanisms under these various factors. Moreover, the keynote is focused on the PVSK film and its contiguous layers to organize corresponding feasible approaches on improving the PVSK photovoltaic lifespan. It is hopeful to pave the way for the PVSK photovoltaic manufacture with long-term stability in diverse aspects.